Pengaruh Profitabilitas, Leverage Dan Ukuran Perusahaan Terhadap Tax Avoidance Pada Perusahaan Manufaktur Sektor Barang Konsumsi Subsektor Makanan Dan Minuman Di Bursa Efek Indonesia Periode 2018-2022 - Anggie. S, Meyliani; Mahpudin, Endang (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study (Study of Manufacturing Companies in the Consumer Goods Sector, Food and Beverage Subsector on the Indonesian Stock Exchange for the Period of 2018–2022) intends to ascertain and investigate the influence of Profitability, Leverage, and Company Size on Tax Avoidance.A purposive selection approach was used to choose the sample from the population of manufacturing businesses in the consumer products sector, food and beverage subsector, listed on the Indonesian stock market for the 2018–2022 period, which totaled 32 companies. Based on predetermined criteria, a total sample of 10 firms was selected in this study. Descriptive statistical analysis, traditional assumption testing, and hypothesis testing using the t test and f test are the data analysis approaches that are employed. The findings of this study demonstrate that: (1) Tax Avoidance (CETR) is unaffected by Profitability (ROA) (X1). The significance value (Sig. ), which is 0.741 > 0.05, demonstrates this. (2) Tax Avoidance (CETR) is unaffected by Leverage (DER) (X2). The significance value (Sig. ), which is 0.981 > 0.05, indicates this outcome. (3) Tax Avoidance (CETR) is somewhat positively impacted by company size (SIZE). The significance value, which is 0.023 0.05, indicates this. (4) Leverage (DER) (X2), Company Size (SIZE) (X3), and Profitability (ROA) (X1) all have an impact on Tax Avoidance (CETR) concurrently. Based on the significance level (Sig.) of 0.043 0.05.